Frontispiece: Solvent‐free Liquid Crystals and Liquids from DNA. Issue 13 (23rd March 2015) - Liu, Kai; Shuai, Min; Chen, Dong; Tuchband, Michael; Gerasimov, Jennifer Y.; Su, Juanjuan; Liu, Qing; Zajaczkowski, Wojciech; Pisula, Wojciech; Müllen, Klaus; Clark, Noel A.; Herrmann, Andreas
<x xml:space="preserve">Abstract</x> Solvent‐free DNA Fluid Systems In the Communication on page 4898 ff., A. Herrmann, N. A. Clark et al. present a simple strategy for producing solvent‐free DNA liquid crystals and liquids by electrostatic complexation of DNA with cationic surfactants. Stable smectic and modulated smectic liquid crystalline phases are obtained by employing surfactants of different alkyl chain lengths. These DNA fluids are stable in the −20°C to 200°C temperature range without thermal degradation of the DNA.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>